2022
DOI: 10.3389/fncel.2022.802192
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Loss and Astrocyte Activation Cause Dynamic Changes in Hippocampal [18F]DPA-714 Uptake in Mouse Models of Depression

Abstract: Major depression is a serious and chronic mental illness. However, its etiology is poorly understood. Although glial cells have been increasingly implicated in the pathogenesis of depression, the specific role of microglia and astrocytes in stress-induced depression remains unclear. Translocator protein (TSPO) has long been considered a marker of neuroinflammation and microglial activation. However, this protein is also present on astrocytes. Thus, it is necessary to explore the relationships between TSPO, mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 84 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…In similar studies on male mice, AIE caused an increase in cluster of differentiation molecule 68 (CD68), indicative of phagocytic activity in microglia in other brain regions, including the dorsal and medial raphe nuclei as well as the dorsal horn or increased Iba1 density in the prefrontal cortex, but the findings are not universal. One study, using a mouse AIE model, observed a loss of hippocampal microglia after AIE, but the animals had also experienced stressful behaviors, which may have been a confounding factor in the microglial expression [44,45]. Moreover, in the same study, re-exposure to ethanol resulted in a bifurcated response with evidence of microglial proliferation concurrent with apoptotic-positive microglia [44].…”
Section: Acute and Chronic Effects Of Adolescent Binge Drinking On Mi...mentioning
confidence: 95%
“…In similar studies on male mice, AIE caused an increase in cluster of differentiation molecule 68 (CD68), indicative of phagocytic activity in microglia in other brain regions, including the dorsal and medial raphe nuclei as well as the dorsal horn or increased Iba1 density in the prefrontal cortex, but the findings are not universal. One study, using a mouse AIE model, observed a loss of hippocampal microglia after AIE, but the animals had also experienced stressful behaviors, which may have been a confounding factor in the microglial expression [44,45]. Moreover, in the same study, re-exposure to ethanol resulted in a bifurcated response with evidence of microglial proliferation concurrent with apoptotic-positive microglia [44].…”
Section: Acute and Chronic Effects Of Adolescent Binge Drinking On Mi...mentioning
confidence: 95%
“…Based on the recent literature, however, the function and expression of connexin 43 in astrocytes increases and decreases in the early and prolonged phases of depression, respectively, and in a chronic unpredictable stress model, the former phase is up to 2 weeks and the latter one is 5 or more weeks. 13,17,37,38) Lu et al demonstrate that in medial prefrontal cortex (mPFC) under stressed conditions, astrocyte activation, which stimulates ATP release via ATP channels, depends on activation of glucocorticoid receptors, and its activity is increased and decreased in the early and chronic phases, respectively, of stress exposure. 13) Although cerebral cortex used in this study included mPFC and thus, their findings not being directly comparable to ours, we suggested that astrocytic expression of connexin 43 and P2X7 receptors in the cerebral cortex might be increased in an early phase of depression, implying the necessity of a disease phase-specific therapeutic approach for ATP channels expressed by cortical astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Changes to astrocytic functions in depression primarily revolve around the neuroimmune state, neuronal transmission, and synaptic plasticity. Astrocytes can become reactive when chronically exposed to stress, which can lead to impairment of their functionalities, including intracellular and extracellular ionic regulation, gap junction-based cellular communication, and neurotransmitter metabolism ( Guo et al, 2022 ; Miguel-Hidalgo, 2022 ). Many studies have indicated that astrocytes play a critical role in regulating various inflammatory signal transductors, such as gp130, transforming growth factor β receptor, interferon-γ receptor, and estrogen receptor α ( Colombo and Farina, 2016 ; Zheng et al, 2021 ).…”
Section: Astrocyte Metabolic Pathways In Neurological Disordersmentioning
confidence: 99%